THE PSYCHO-SOCIAL FEATURES OF DEVELOPING TOLERANCE OF STUDENTS IN THE PROCESS OF ACCULTURATION (Uzbek Scholar Journal, 2022)
The relevance of the study is reasoned by the objective necessity in the education of students, focused on humanistic values and able to engage in dialogue with society. The purpose of the paper is to reveal the students’ tolerant behavior formation mechanisms. The guiding principle of investigation is the event-related principle, providing students’ inclusion in the set of events that encourage awareness of the sense of tolerance and aimed at creating of capacity for tolerant behavior. Tolerant and intolerant attitudes are a most current subject following the recent global rise in refugees being forced to relocate across the world. The aim of this study is to investigate tolerance and its development over time in adolescents. An important focus is how tolerance, intolerance and intolerant behaviors relate to one another and whether there are different developmental trajectories as well as subgroups.